HUBUNGAN FAKTOR INTRINSIK DENGAN KEJADIAN RESIKO JATUH PADA LANSIA DI WILAYAH KERJA PUSKESMAS HANDAPHERANG KABUPATEN CIAMIS - taufik hidayat; jajuk kusmawaty; nur hidayat (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2019)
These changes affect the physical fatigue, joint pain, balance disorders and coordination. This condition is exacerbated by blurred vision, poor hearing, adaptation disorders, and the effects of consumption of certain drugs that all result in the risk of falling in the elderly. There are several risk factors that fall one of them intrinsic factors are hypertension disorders, impaired limb system, nervous system disorders, impaired vision, and hearing loss.The method in this research is quantitative analit by using cross sectional approach. The population in this researchis all elderly in Working Area of Health Unit of Puskesmas Handherang of Ciamis Regency in year 2017 as many as 6587 people Sample as many as 99 people.The results showed that intrinsic factors mostly categorized as many as 57 people (57.6%), the risk incidence of falling in the elderly most categorized the risk of falling as high as 56 people (56.6%) and there is a significant relationship between intrinsic factors with events the risk falls on the elderly because the value of ?> ? value (0.05> 0,000) and the value of chi square (?2)counts> chi square (?2) table (65,705> 5,991). Suggestions are expected for elderly to improve healthy lifestyle so as to decrease the risk incidence of falling inthe elderly.